2019
DOI: 10.1111/cdev.13311
|View full text |Cite
|
Sign up to set email alerts
|

Indian = Hindu? The Development of Nationalist Attitudes Among Hindu and Muslim Children in India

Abstract: This is the author manuscript accepted for publication and has undergone full peer review but has not been through the copyediting, typesetting, pagination and proofreading process, which may lead to differences between this version and the Version of Record. Please cite this article as

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 52 publications
0
3
0
Order By: Relevance
“…Future research could also explore the intersection of a broader range of social categories (e.g., religion, language; Ellwood‐Lowe et al., 2020) and other aspects of children's identities (e.g., skin tone) in shaping leadership cognition. The present findings underscore that children's developing leadership cognition reflects intersectional considerations, and future research might unpack these patterns further (see also Ghavami et al., 2016; Santos & Toomey, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Future research could also explore the intersection of a broader range of social categories (e.g., religion, language; Ellwood‐Lowe et al., 2020) and other aspects of children's identities (e.g., skin tone) in shaping leadership cognition. The present findings underscore that children's developing leadership cognition reflects intersectional considerations, and future research might unpack these patterns further (see also Ghavami et al., 2016; Santos & Toomey, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…They found that children's friendship networks tended to be segregated on the basis of religion, and that the internalization of the association between religion and nationalism was associated with social segregation of religious groups. However, they caution against pessimistic conclusions suggesting that 'even in a region a history of religious conflicts, and among children who exhibit intergroup religious bias, it is possible for minority children to develop inclusive associations and beliefs of what it means to be a citizen of their country' (Ellwood-Lowe et al 2019: 1391. The ongoing protests against the CAA have demonstrated that some issues are capable of bringing together people of different belief systems and faiths.…”
Section: Devleena Ghosh Lola Sharon Davidsonmentioning
confidence: 99%
“…In the context of religions and their nation‐states, Christians in the United States often associate Christianity with being an American (Butz & Carvalho, 2015; Jacob & Theiss‐Morse, 2013). Similarly, many Hindus in India associate Hinduism with their national identity (Ellwood‐Lowe et al., 2019).…”
Section: In‐group Prototypicality and Support Of Subgroup–superordina...mentioning
confidence: 99%